2020
DOI: 10.1140/epjc/s10052-019-7472-2
|View full text |Cite
|
Sign up to set email alerts
|

Extended Higgs sector of 2HDM with real singlet facing LHC data

Abstract: We study the phenomenology of the two Higgs doublet model with a real singlet scalar S (2HDMS). The model predicts three CP-even Higgses h1,2,3, one CP-odd A 0 and a pair of charged Higgs. We discuss the consistency of the 2HDMS with theoretical as well as with all available experimental data. In contrast with previous studies, we focus on the scenario where h2 is the Standard Model (SM) 125 GeV Higgs, while h1 is lighter than h2 which may open a window for Higgs to Higgs decays. We perform an extensive scan i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
15
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(15 citation statements)
references
References 64 publications
0
15
0
Order By: Relevance
“…We have assumed small values of α 2 and α 3 so that we can utilize the existing bound on the parameters like α and β of a two Higgs doublet model (2HDM) scenario with and without an additional singlet. For recent analyses of extended 2HDM see [93][94][95][96][97]. It has been shown that large singlet doublet admixture is allowed by the LEP and LHC data [95].…”
Section: Jhep12(2020)052mentioning
confidence: 99%
“…We have assumed small values of α 2 and α 3 so that we can utilize the existing bound on the parameters like α and β of a two Higgs doublet model (2HDM) scenario with and without an additional singlet. For recent analyses of extended 2HDM see [93][94][95][96][97]. It has been shown that large singlet doublet admixture is allowed by the LEP and LHC data [95].…”
Section: Jhep12(2020)052mentioning
confidence: 99%
“…Upon substituting in the current values of the standard parameters entered in the expression above, i.e., M Z ¼ 91. 18…”
Section: B Some Constraintsmentioning
confidence: 99%
“…We find the whole set of conditions and pave the way for similar models. We follow the techniques employed in [18].…”
Section: A Bound From Below Conditionsmentioning
confidence: 99%
“…The vacuum stability bounds for the model with the two scalar doublets and a complex scalar singlet of the model with type I seesaw mechanism in section 2 can be found following the same steps of Ref. [61], where it was treated the case with a real singlet. The analysis will be also useful next when dealing with the potential of the type II seesaw mechanism.…”
Section: A1 Vacuum Stability Bounds For the 2hdm-u(1) With Type I Sementioning
confidence: 99%